Microstructure, thermodynamics and compressive properties of AlCrCuNiZrx (x = 0, 1) high-entropy alloys. Issue 12 (12th August 2016) - Wang, Xiao-Rong; Wang, Zhao-Qin; Lin, Tie-Song; He, Peng
Abstract : Two high-entropy alloys (HEAs), AlCrCuNiZr x ( x = 0, 1), were prepared by arc melting. The AlCrCuNi alloy consists of a face centered cubic (FCC) phase, a body centered cubic (BCC) phase and an eutectic phase, while the AlCrCuNiZr alloy contains a FCC phase, a BCC phase and an intermetallic phase. The traditional thermodynamic parameters of HEAs were converted into thermodynamic-parameter-functions of composition variable x, including Δ G mix ( x ), Δ H mix ( x ), Δ S mix ( x ), Ω ( x ), δ( x ), Δχ( x ) and VEC ( x ). The thermodynamic-parameter-curves could be obtained through thermodynamic-parameter-functions via Matlab. The thermodynamics of the two alloys were analysed using the thermodynamic-parameter-curves of the AlCrCuNiZr x ( x ∈[0 1]) alloys. The addition of Zr to AlCrCuNiZr favours the formation of intermetallic compound, enhances the yield strength, compressive strength and Vickers hardness, but degrades ultimate strain.